'Stay at home and limit contact': The impact of stay‐at‐home advice on the behavior of Australian donors aged 70 and over in the first year of the pandemic. Issue 12 (7th October 2022) - Naing, Sanda; Thorpe, Rachel; Jensen, Kyle; Masser, Barbara; Guerin, Nicola
Abstract: Background: Early in the COVID‐19 pandemic, Australian donors aged 70 and over were advised to temporarily stop donating. The aim of this research was to understand the factors associated with some of these donors continuing to donate despite the advice, and whether adherence to the advice had negative implications for donor retention. Study Design and Methods: Survey data from 2078 donors were analyzed to understand the factors associated with donating blood during the first 6 months of the pandemic, and the impact of following stay‐at‐home advice during the first 6 months of the pandemic on donor return 6–12 months into the pandemic. Panel data were used to gain an overview of donation behavior before, during, and after the initial phase of the pandemic. Results: Donations by donors aged 70 and over decreased disproportionately to other age groups during the early stages of the pandemic. Sex, total donation count, awareness of stay‐at‐home advice from the Blood Collection Agency, the mode of receiving stay‐at‐home advice, donor risk perceptions and attitudes toward stay‐at‐home advice were associated with donation behavior in the first 6 months of the pandemic. Donors who did not donate in the first 6 months of the pandemic had lower odds of returning 6–12 months into the pandemic. Conclusion: Stay‐at‐home advice was partially successful in preventing older donors from donating; however, more tailored communication approaches may have prevented more donors from donating. Implementation of stay‐at‐home advice should be accompanied by strategies to prevent ongoing donor lapse in the medium‐ to long‐term.